Problems of technical and linguistic employment in making news reports on Iraqi satellite television channels“An analytical study into the artistic and linguistic use of the visual reports of the Iraqi and Al-Sharqiya news channels.” - Heba Kazem Musa , Lect.; Arshad Yassin Aday Al-Zuhairi, Dr. (lark, 2024)
The research dealt with, “Forms of artistic and linguistic employment in the production of visual reports: A study in the verbal employment features of the language I bring.” Visible from a media point of view” in terms of the use of words and the new linguistic punctuation. The vocabulary is in its correct place from a media point of view, as a result of the reason that reporters specialize in using vocabulary incorrectly. In addition to the technical mistakes that the reporter, photos, and the editing engineer, and other journalistic staff, overlook. When preparing and making television reports.Therefore, the researcher used the descriptive approach to describe the reports and analyze them based on an integrated, academic media vision. The research reached a number of results, namely that most of those involved in making reports are not guided based on a plan in the context of work when making and preparing the report, as Al-Jazeera channels do. With its channels, and the BBC channel with its channels), the report making industry is subject to the use of multiple arts and different visions, so it is sometimes difficult for the reporter to collect all the contradictions and anomalies and implement the impossible in the television report, as he works according to what exists in reality. Also, some Reporters carry out the process of making television reports in a way that relies only on the photographer, meaning that most of the reporters have not been to the field of work.